Pola Kasus Onkologi-Ginekologi di Bangsal Ginekologi RSUD Zainoel Abidin 2021-2022 - Alfatah, Ridwan; Salmah, Salmah; Khalisa, Ighra; Nora, Hilwah (Penerbit Goodwood, 2025)
Purpose: This study aimed to determine the pattern of oncological and gynecological cases in the Gynecological Inpatient Room at RSUD Zainoel Abidin for the period June 2021-June 2022.. Methodology: This descriptive retrospective study obtained data from the inpatient register book by identifying age, domicile, diagnosis, action, length of treatment, and outcomes after treatment for the period June 2021-June 2022. Results: A total of 514 patients met the inclusion criteria, with 139 having oncology and the remaining gynecological issues. The largest age groups for oncology patients were 50-59 years (36.69%) and for gynecology, 40-49 years (42.40%), respectively. Most of the patients were from Aceh Besar (15.56%, 80 patients). Ovarian carcinoma was the most common oncology case (57.55%), whereas uterine myomas were the most common in gynecology (27.73%). Of these, 343 (66.73%) underwent laparotomy. The highest number of admissions occurred in January 2022 (11.48%), with an average hospital stay of 7.39 days for oncology and 6.43 days for gynecology. Of the patients, 87.94% were discharged alive and 1.17% died. Conclusion: This study found that most gynecological inpatients treated at RSUD Zainoel Abidin had leiomyoma utery (age range–40-49 and underwent laparotomy with an average length of stay of 13.35 days and good outcome. Limitations: The limitations of this study include the retrospective method, data coverage from only one hospital, and reliance on secondary records that may not always be complete or consistent. Contribution: This study can contribute to the optimization of hospital policies related to the management of oncology-gynecology patient care.